2017
DOI: 10.9734/bjpr/2017/32524
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students Perception and Practice of Self-medication: Vision of Future Practitioner in Pakistan

Abstract: Aims: The present study was conducted to explore self-medication among the medical students and their perception towards self-medication in four medical colleges in Abbottabad, Pakistan. Study Design: The study was carried out as a cross sectional survey. Place and Duration of Study: The study was carried out in four medical colleges during the period from April to September 2016 in Abbottabad, Pakistan. Methodology: A semi structured questionnaire was developed. The questionnaire consisted of 6 sections. Firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…This finding is comparable with studies carried out in Mekelle University, Ethiopia, 5 Taibah University, Saudi Arabia, 11 Nagpur India, 12 North India, 38 and Pakistan. 39 This could be as the students' year of study increases, they take more practical-oriented courses. Hence, their knowledge and understanding about drugs and diseases would also increase, which resulted in high uptake and purchase of medication without prescription since the regulatory system is loose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is comparable with studies carried out in Mekelle University, Ethiopia, 5 Taibah University, Saudi Arabia, 11 Nagpur India, 12 North India, 38 and Pakistan. 39 This could be as the students' year of study increases, they take more practical-oriented courses. Hence, their knowledge and understanding about drugs and diseases would also increase, which resulted in high uptake and purchase of medication without prescription since the regulatory system is loose.…”
Section: Discussionmentioning
confidence: 99%
“…36 Several studies revealed a range of factors that affect selfmedication practice. Accordingly, the socio-demographic factors include sex, 1,5,7,11,14,28,32,34,37 age, 18,23,32,34,37 monthly income, 14,23,29,37 level of education, 32,37 residence, 15,34 religion, 15 marital status, 7,29,34,38 year of study, 5,[10][11][12]32,38,39 and field of study. 1,5,11,12,14,23 Moreover, the source of drugs for self-medication such as community pharmacies, 6,15,23,29,32 drug stores, 16,32 unused drugs stored at home, 11,…”
Section: Introductionmentioning
confidence: 99%
“… 14–16 Moreover, these practices vary according to each student’s socio-demographic characteristics including age, gender, socio-economic status, educational level, residence, and field of study. 17 …”
Section: Introductionmentioning
confidence: 99%